Polymer/Palmitic Acid Blends as Shape-Stabilized Phase Change Material for Latent Heat Thermal Energy Storage - Sari, Ahmet; Karapekl, Ali; Akaay, Murat; Onal, Adem; Kavak, Ferda (Asian Journal of Chemistry, 2010)
Two composite blends of poly(vinyl alcohol)-palmitic acid and poly(vinyl chloride)-palmitic acid were prepared. In these composites, palmitic acid acts as latent heat energy storage during its solid-liquid phase change when the polymer (poly(vinyl chloride) or poly(vinyl alcohol)) has the function of supporting material because of its structural strength. There is no leakage of palmitic acid even when it is in melt state. Therefore, these composite blends are called shape-stabilized phase change materials and they have utility advantage of without encapsulation in passive solar latent heat thermal energy storage application. The maximum percentage miscibility ratio of palmitic acid with both polymers was found as 50 as the blends have the shape-stabilized property. The dispersion of palmitic acid into the network of polymer matrix was investigated using a dissection microscope. The miscibilities of palmitic acid with poly(vinyl alcohol) and poly(vinyl chloride) were proved by Fourier transfer infrared spectroscopy and differential scanning calorimetry methods. Furthermore, the melting temperatures and latent heats of both the shape-stabilized composite blends were determined as 56.2 and 54.4°C and 121.6 and 120.3 J/g, respectively. The results obtained indicate that the shape-stabilized composite blends have great potential for passive solar space heating and solar building heating in terms of their satisfactory thermal properties and cost-effectivity.